2015
DOI: 10.1002/smj.2367
|View full text |Cite
|
Sign up to set email alerts
|

New product introductions below aspirations, slack and R&D alliances: A behavioral perspective

Abstract: We develop hypotheses based on behavioral theory that explain how high technology firms' new product introduction (NPI) performance below aspiration levels impact the number of R&D alliances, and how slack moderates this relationship. Using panel data of U.S. biopharmaceutical firms, we find that as firms' NPI performance below historical aspiration levels increases the number of R&D alliances they form increases and slack intensifies this relationship. We contribute to alliance research by providing theory an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
154
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(158 citation statements)
references
References 88 publications
(151 reference statements)
3
154
1
Order By: Relevance
“…While we expect general support for a positive relationship in line with prior meta‐analyses, the continuing presentation of mixed empirical evidence (e.g., Haleblian et al, ; Kim et al, ; Lecuona and Reitzig, ; McClelland et al, ; Tang et al, ; Tyler and Caner, ) suggests that our models linking slack to performance are limited. We address this issue by detailing the role competitive behaviours play in transforming and directing the utilization of slack for performance gains.…”
Section: Theory and Hypothesessupporting
confidence: 65%
“…While we expect general support for a positive relationship in line with prior meta‐analyses, the continuing presentation of mixed empirical evidence (e.g., Haleblian et al, ; Kim et al, ; Lecuona and Reitzig, ; McClelland et al, ; Tang et al, ; Tyler and Caner, ) suggests that our models linking slack to performance are limited. We address this issue by detailing the role competitive behaviours play in transforming and directing the utilization of slack for performance gains.…”
Section: Theory and Hypothesessupporting
confidence: 65%
“…Finally, a third assumption relates to the window over which an alliance portfolio is defined. Consistent with the approach taken in a number of recent alliance studies (e.g., Bos, Faems, & Noseleit, 2017;Cui, Yang, & Vertinsky, 2018;Tyler & Caner, 2016;Van de Vrande, 2013;Yang, Lin, & Peng, 2011), I use a 5-year window to recognize that alliances continue beyond just the year in which they were established, but that they are at the same time finite in their lifespan.…”
Section: Operationalizing Capacity-constrained Resource Congestionmentioning
confidence: 99%
“…Finally, as Anderson et al (2004) suggested, it may prove interesting to study innovation as an independent rather than a dependent variable. Among studies adopting this approach, Tyler and Caner (2016) examined how the success or failure of new product introduction affects the likelihood of new R&D alliance formation. Based on the above, it seems reasonable to argue that innovation is a process, even when only outcomes are measured.…”
Section: Turning Challenges Into Opportunities For Im Researchmentioning
confidence: 99%